PRODUKTIVITAS TENAGA KERJA PEMANEN DI PT PERKEBUNAN NUSANTARA VII UNIT KEBUN KELAPA SAWIT REJOSARI - Adyguna WF Simamora; Wuryaningsih Dwi Sayekti; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The aims of this research were to know the productivity of labors of palm fruit reaper and its influencing factors in PT Perkebunan Nusantara VII Unit Rejosari Palm Plantation.  This research was conducted at PT Perkebunan Nusantara VII Unit Rejosari Palm Plantation, Natar Subdistrict, South Lampung Regency. The data was collected from April – May 2015 by survey method. The total respondents for this research were 54 people which were chosen by systematic random sampling method.  Analysis method used in this research was quantitative descriptive and multiple linear regression analysis. The result of this research showed that the productivity of labors of palm fruit reaper at PT Perkebunan Nusantara VII Unit Rejosari Palm Plantation in 2015 was 732.68 kg per day or about 106.71 percent from the target, this was included as insufficient category. The influencing factors on the productivity of labors of palm fruit reaper at PT Perkebunan Nusantara VII Unit Rejosari Palm Plantation were salary and incentive, nutrition and health, education and training; whereas, motivation, age and years of service did not signicantly affect it. Key words: labors, palm fruit, productivity